Is the aortic size index relevant as a predictor of abdominal aortic aneurysm? A population-based prospective study: the Tromsø study. (3rd March 2020) - Nyrønning, Linn Åldstedt; Skoog, Per; Videm, Vibeke; Mattsson, Erney
Abstract: Objectives. The normal aortic diameter (AD) varies with gender, age and body surface area (BSA). The aortic size index (ASI) is defined as the AD divided by BSA. The primary aim of this study was to investigate if ASI is a predictor of development AAA, and to compare the predictive impact of ASI to that of the absolute AD. Design . Population-based prospective study including 4161 individuals (53.2% women) from the Tromsø study with two valid ultrasound measurements of the AD and no AAA at baseline (Tromsø 4, 1994). The primary outcome was AAA (AD ≥30 mm) in Tromsø 5 (2001). A secondary outcome was aortic growth of >5 mm over 7 years. Estimates of relative risk were calculated in logistic regression models. The main exposure variable was ASI. Adjustments were made for age, gender, smoking, body mass index, total and high-density lipoprotein (HDL) cholesterol, and hypertension. Results . In total, 124 incident AAAs (20% among women) were detected. In adjusted analyses, both ASI and AD were strong predictors of AAA, with similar results for men and women. Both ASI and AD were also significant predictors of aortic growth >5 mm. In comparison, AD was superior to ASI as a predictor of both endpoints. Conclusions . ASI was a significant predictor of both AAA development and aortic growth of >5 mm for both men and women, but not a better predictor of either outcomes compared to the AD. The role of ASI compared to the AD as a predictor of AAA development seems to be limited.